Application cns / atm for effective methods of reducing aircraft noise when the aircraft before boarding - Запорожець, О.І.; Бабейчук, Д.Г. (Proceedings of National Aviation University (archive), 2008)
CNS/ATM implementation in flight management is investigated as a mean for upport of effective operational procedures for aircraft noise control around the airports.